Effect of microwave and ultrasonic irradiation on the enzymatic hydrolysis of water hyacinth biomass in the presence of surfactants - Rokhati, Nur; Ratnawati; Prasetyaningrum, Aji; Anggraini, Widyah; Nugroho, Akbar; Novita, Nasyriyatul Hana; Andarani, Pertiwi; Riyanto, Teguh (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2023)
This paper presents the effect of microwave and ultrasound irradiation on the enzymatic hydrolysis of water hyacinth biomass in the presence of surfactants. Prior to hydrolyzing, the water hyacinth was treated utilizing alkali with and without microwave assistance. It was revealed that the microwave improved the removal of lignin and hemicellulose. The treated water hyacinth biomass was also characterized using Scanning Electron Microscope (SEM), X-ray Diffraction (XRD), and Fourier-Transform Infrared (FT-IR) Spectroscopy. The effect of surfactant and the assistance of microwave and ultrasound were comprehensively studied. Some parameters varied, including stirring speed, surfactant type, concentration, and reaction time. The results indicated that microwave and ultrasound could enhance the reaction rate. Tween 80 here could improve conventional, microwave-assisted, and ultrasound-assisted hydrolysis of water hyacinth biomass. It was found that the ultrasound-assisted hydrolysis was better than that of others. The results of this research can be used as the groundwork for further developing the lignocellulosic biomass hydrolysis process, especially in an advanced enzymatic hydrolysis process.